2022
DOI: 10.1002/jemt.24189
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of bioactive polyvinylpyrrolidone film via electrospinning technique

Abstract: Electrospinning technique became a very common and effective method to fabricate nonwoven films with a large surface area for different purposes especially in the biomedical field. Antimicrobial submicron fibrous films based on polyvinylpyrrolidone (PVP) doped with silver nanoparticles (Ag-NPs), Zinc Oxide (ZnO), and (Ag-NPS/ZnO), were successfully fabricated via the electrospinning technique. The morphology and the elemental configurations of the as-prepared films were studied by using scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Abdelhafiz et al investigated polyvinylpyrrolidone (PVP) film doped with silver and zinc oxide nanoparticles. They reported that the presence of the nanoparticles increased the fiber diameter of the PVP polymer film [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdelhafiz et al investigated polyvinylpyrrolidone (PVP) film doped with silver and zinc oxide nanoparticles. They reported that the presence of the nanoparticles increased the fiber diameter of the PVP polymer film [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Kirby–Bauer disc diffusion method was applied to test the antibacterial activity of the scaffolds containing different salts [ 46 47 ]. The experiment was performed using four bacterial strains (American Type Culture Collection, ATCC): E. coli (Gram-negative), P. aeruginosa (Gram-negative), S. epidermidis (Gram-positive), and B. subtilis (Gram-positive).…”
Section: Methodsmentioning
confidence: 99%